PENGEMBANGAN MEDIA VIDEO POWTOON PADA PEMBELAJARAN TEMATIK TERPADU BERBASIS MODEL PROBLEM BASED LEARNING (PBL) DI KELAS IV SEKOLAH DASAR - Anggelia Putri; Reinita Reinita (LPPM Universitas Muhammadiyah Muara Bungo, 2022)
This study aims to develop a video powtoon media in integrated thematic learning based on the Problem Based Learning (PBL) modeI in grade IV Elementary School which is valid and practical. The type of research conducted is Research and Development (R&D) with a 4D development model Phase 1, namely Define, stage II Design, stage III Develop, stage IV namely Disseminate, at stage Disseminate the researcher did not do it because of time and cost limitations. So the researchers only carried out until the development stage (develop). The results of the research on Video Powtoon Media Development that were developed obtained the results of the material validity test getting a percentage of 93%, the results of the language validity test being 87.5%, and the media validity test results being 92.85%. While the results of the practicality test of the teacher's response questionnaire obtained results of 87.50% and the results of the practicality test of the student's response questionnaire obtained the results of 88.96%. Thus it can be concluded that the Video Powtoon Media in integrated thematic learning in grade IV Elementary School has been valid and practical to use.